Development of printable material with recycled glass for 3D concrete printing - Ting, Andrew Guan Heng (Nanyang Technological University, 2022)
Although glass can be recycled indefinitely without any degradation in quality to manufacture new glass products, it is required for the glass to be processed and sorted into different colours to prevent any contamination and chemical incompatibility. However, glass waste is often co-mingled with other types of waste and can be very costly and challenging to be recycled, thus resulting in a low recycling rate. Glass waste that is not recycled usually ends up in landfills, a rapidly becoming scarce resource. Moreover, glass being an inert material is non-biodegradable and can remain in the land indefinitely if disposed into landfills. With the fourth industrial revolution, there is also a need for the construction industry to adopt automation into building activities. 3D concrete printing is an innovative process of selectively depositing concrete material at a pre-specified path through a digital model, reducing the material wastage and significantly shortening the time to fabricate a construction element. Moreover, the complex design obtained from computer-aided-design (CAD) modelling can be easily printed in a short time. The state-of-the-art technology utilizes river sand as the aggregates in the mixture. The exploitation of river sand is at a higher rate than it can be replenished naturally due to the high demand for construction materials, resulting in a depleting supply. Sand mining activities endanger the local surrounding ecosystem of the river. The investigation of recycled glass as an alternative to river sand was conducted in this research with the aim of a sustainable printable concrete material. The development of the printable material with recycled glass allows the reduction or elimination of river sand as a constituent for 3DCP. The effects of recycled glass cullets as fine aggregates for the material in construction 3D printing was studied. Results show that the static yield stress decreases while the dynamic yield stress and plastic viscosity increase as the recycled glass cullets content increases. The change in rheological properties also affected the printability of the mixtures. In the mechanical properties test, the increase in recycled glass cullets content also reduces the compressive strength and interlayer bond strength of the specimens. The concrete needs to possess high initial yield stress to maintain its shape upon extrusion and the weight of the subsequent layers during the early stage of the printing process. However, the high yield stress of the concrete results in the excessive effort required to extrude the concrete and leads to defects on the surface of the filament. The effects of various material parameters on the extrudability and buildability of the recycled glass concrete to determine the extrudable region of the concrete mix design using a graphical approach. The results show that the mix designs at the extrudable limit surface are most optimal for 3D concrete printing as it has the maximum buildability with the extrudable region. The buildability of the concrete is dependent on the structural build-up properties of the concrete. The rapid structuration rate allows the initial layer to gain strength to support the above layers and prevent strength-based structural failure. The required structuration rate of the concrete is dependent on the building rate of the structure which is process parameters dependent. The behaviour of the concrete with various structuration rates under different process parameters was examined using the mechanical compression test. The mechanical compression test is proposed to simulate the compression load of the building layers on the initial layer. The relationship between the structuration rate of the concrete and the building rate of the printing process is determined. A printable support material that temporarily supports the overhang sections was developed with sustainable raw materials such as fly ash and recycled glass powder. The support material should also allow ease of removal after the primary material is hardened. Results indicate that the recycled glass powder reduces the pumpability but increases the buildability of the support material. Excessive recycled glass powder content also caused clogging in the material delivery system. An optimal mix design was determined by the response optimizer. The optimal mix design was used to print a structure with a free form overhang section as a proof-of-concept.